1984
DOI: 10.1007/bf01852379
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenesis during sepsis in relation to hepatic energy metabolism

Abstract: The concentrations of acetoacetate, beta-hydroxybutyrate, and adenine nucleotides, and the mitochondrial phosphorylative activities, induced by cecal ligation and punctured in the liver of septic rats, were determined. The concentrations of glucose, free fatty acids (FFA), and free amino acids in arterial blood were also studied along with ketone body concentrations. Hepatic energy charge levels decreased from 0.84 to 0.77 at 12h after the induction of sepsis (P less than 0.01) and to 0.60 at 18h (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
13
2
Order By: Relevance
“…This initial increase in respiratory activity followed by a later decrease was also found by Ohtoshi et al in septic rats [64]. Mitochondrial phosphorylation activity was enhanced at 6 h (PϽ0.001), but decreased at 18 h. Hepatic energy charge levels fell from 0.84 to 0.77 at 12 h (PϽ0.01) and to 0.60 at 18 h (PϽ0.001).…”
Section: Initial Increase Later Decreasesupporting
confidence: 77%
See 1 more Smart Citation
“…This initial increase in respiratory activity followed by a later decrease was also found by Ohtoshi et al in septic rats [64]. Mitochondrial phosphorylation activity was enhanced at 6 h (PϽ0.001), but decreased at 18 h. Hepatic energy charge levels fell from 0.84 to 0.77 at 12 h (PϽ0.01) and to 0.60 at 18 h (PϽ0.001).…”
Section: Initial Increase Later Decreasesupporting
confidence: 77%
“…Sepsis-induced elevations in cytosolic Ca 2ϩ have been well described [57,64,78,79], although Ohtoshi et al found markedly higher Ca 2ϩ levels in septic liver mitochondrial fractions [64]. Deaciuc and Spitzer found a slight, but significant, increase in total hepatic Ca 2ϩ content with sepsis [80]; although a decrease was noted in Ca 2ϩ content in the microsomal fraction, there was an increase in mitochondrial content.…”
Section: Calciummentioning
confidence: 98%
“…Lower liver carnitine concentration is reported in those premature infants who receive more than 15 days of total parenteral nutrition34 and in the case of a boy with extremely low level of plasma carnitine, isolated muscle mitochondria showed decreased oxidative capacity with respect to all substrates. 3,5 In the present study, carnitine level was not measured and it may be possible that in the TPN group, carnitine level was decreased and the long-chain acyl-CoA was increased. The decrease in phosphorylative activity observed in the present may be ascribed to carnitine deficiency because the long-chain acyl-CoA inhibits the adenosine nucleotide transloca-…”
Section: Discussionmentioning
confidence: 68%
“…In critical illness, however, although plasma glucagon, cortisol, and catecholamines are elevated, concomitant hyperinsulinemia and hyperglycemia may suppress ketogenesis [20,21]. In line with this, available data, though scarce, suggested suppressed ketogenesis during critical illness [22][23][24][25]. Withholding early-PN has shown to reduce the degree of hyperglycemia, to lower the insulin requirements to prevent hyperglycemia [4,5], and to lower the insulin/glucagon ratio [26].…”
Section: Introductionmentioning
confidence: 99%